Facile one-pot electrosynthesis of zinc hydroxide for the adsorption of hazardous 2-(2-methyl-4-chlorophenoxy) propionic acid (MCPP) from water and its modelling studies. Issue 2 (April 2018) - Kamaraj, Ramakrishnan; Pandiarajan, Aarthi; Vasudevan, Sudharshan; Vasudevan, Subramanyan
Graphical abstract: Highlights: MCPP was removed efficiently by one-pot electrosynthesised zinc hydroxide. Adsorption equilibrium follows pseudo-second-order model. Equilibrium data were well described by the typical Langmuir adsorption isotherm. Thermodynamic studies revealed that the adsorption reaction was spontaneous. Abstract: This present research work investigates the adsorption of hazardous 2-(2-methyl-4-chlorophenoxy) propionic acid (MCPP) from water using electrochemically synthesized zinc hydroxide material. In order to compute the conditions of higher adsorption efficiency, the various parameters such as pH, temperature, current density and the concentration of the contaminant, and inter-electrode distance were studied. The obtained results were analysed by modeling studies viz. Langmuir, Freundlich, D-R isotherm, and Temkin isotherms. The Langmuir isotherm confirms that the monolayer adsorption of 2-(2-methyl-4-chlorophenoxy) propionic acid molecule on the surface of zinc hydroxide. The adsorption mechanism was studied by pseudo-first order, second-order, Elovich model Weber and Morris intraparticle diffusion models. The adsorption of MCPP on zinc hydroxide follows the second-order kinetic model. Based on the heat effect of adsorption, the thermodynamic parameter via enthalpy, entropy, and free energy was evaluated. The calculated thermodynamic parameters endorse that the adsorption was endothermic, spontaneous and thermodynamically feasible.